Pengaruh program gerakan literasi sekolah terhadap minat baca siswa SD se-kecamatan laweyan kota surakarta - Vetrisya, Ayu; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2024)
This study aims to analyze how much influence the School Literacy Movement program has on the reading interest of elementary school students in Laweyan District, Surakarta City. This research is a correlational quantitative research. The data source for this research was fifth grade students at SD Laweyan Surakarta. The sampling technique was carried out by purposive sampling. Data collection was carried out using a closed questionnaire. The validity test uses internal/expert assessment validity, external/empirical validity with trials, and construct validity with Confirmatory Factor Analysis (CFA). Data analysis consisted of analysis prerequisite tests and hypothesis testing. The analysis prerequisite test consists of a normality test and a linearity test, while the hypothesis test uses a simple correlation test, simple regression test, and analysis of the coefficient of determination. The results of this study are as follows: First, simple correlation analysis shows a positive correlation, seen from the Pearson Correlation of 0.223 and a significance level of 0.021. Based on the interpretation of the correlation coefficient, the level of association between the school literacy movement and reading interest is low (0.223), which is in the range of 0.20-0.399. Second, based on simple regression analysis, Y' = 28.315 + 0.251 X indicates that the regression coefficient for the School Literacy Movement (X) is 0.251, meaning that if the School Literacy Movement increases by 1, then Reading Interest will increase by 0.251. The coefficient is positive, meaning that there is a positive relationship between the School Literacy Movement and Reading Interest. Third, based on the analysis of the coefficient of determination shows that the coefficient of determination (R²) of the School Literacy Movement variable on Reading Interest is 0.050. This means that the effect of the School Literacy Movement on Reading Interest is 5% while the rest is influenced by other variables.